Managing military training-related environmental disturbance. (15th December 2017) - Zentelis, Rick; Banks, Sam; Roberts, J. Dale; Dovers, Stephen; Lindenmayer, David
Abstract: Military Training Areas (MTAs) cover at least 2 percent of the Earth's terrestrial surface and occur in all major biomes. These areas are potentially important for biodiversity conservation. The greatest challenge in managing MTAs is balancing the disturbance associated with military training and environmental values. These challenges are unique as no other land use is managed for these types of anthropogenic disturbances in a natural setting. We investigated how military training-related disturbance is best managed on MTAs. Specifically, we explored management options to maximise the amount of military training that can be undertaken on a MTA while minimising the amount of environmental disturbance. MTAs comprise of a number of ranges designed to facilitate different types of military training. We simulated military training-related environmental disturbance at different range usage rates under a typical range rotation use strategy, and compared the results to estimated ecosystem recovery rates from training activities. We found that even at relatively low simulated usage rates, random allocation and random spatial use of training ranges within an MTA resulted in environmental degradation under realistic ecological recovery rates. To avoid large scale environmental degradation, we developed a decision-making tool that details the best method for managing training-related disturbance by determining how training activities can be allocated to training ranges. Highlights: Military training related environmental disturbance was simulated at different range usage rates. Even at low usage rates, unmanaged use of all MTA ranges will result in environmental degradation. A decision making tool detailing the best method for managing environmental disturbance was developed.